Editorial, Vol. 13 Issue 2: Special Issue on Diversity, Inclusion, and Equity in Financial Therapy - Wookjae Heo; Abed Rabbani (Journal of Financial Therapy, 2022)
We are honored to present the special issue of diversity, equity, and inclusion in financial therapy, as JFT’s second issue of volume 13, 2022.